2011
DOI: 10.1093/humrep/der110
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reproductive tract environment following controlled ovarian hyperstimulation treatment on embryo development and global transcriptome profile of blastocysts: implications for animal breeding and human assisted reproduction

Abstract: background: In mammals, the reproductive tract plays a crucial role in the success of early reproductive events and provides an optimal microenvironment for early embryonic development. However, changes in the reproductive tract environment associated with controlled ovarian hyperstimulation and the influence on the embryo transcriptome profile have not been investigated. Therefore, we investigated differences in the development rate and the transcriptome profile of bovine blastocysts developing in the reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 77 publications
1
58
0
Order By: Relevance
“…It has been reported that the condition of the oviduct where bovine embryos were placed until reaching the blastocyst stage influenced their gene expression patterns, especially for those genes that regulate metabolic activity (Gad et al 2011). Thus, factors from the oviductal secretion could affect the embryo gene expression.…”
Section: R7mentioning
confidence: 99%
“…It has been reported that the condition of the oviduct where bovine embryos were placed until reaching the blastocyst stage influenced their gene expression patterns, especially for those genes that regulate metabolic activity (Gad et al 2011). Thus, factors from the oviductal secretion could affect the embryo gene expression.…”
Section: R7mentioning
confidence: 99%
“…3). The oviduct plays an important role in gamete maturation, gamete transportation, fertilization, and preimplantation development (Ellington 1991, Barriere et al 2002, Lyons et al 2006, Brussow et al 2008, Kolle et al 2010, Gad et al 2011. Therefore, some factors in the oviduct may activate embryonic mitochondria and protect them from oxidative stress (Figs 3 and 5).…”
Section: Female Nomentioning
confidence: 99%
“…Taking into account the steroid inactivation role of the HSD17B4 protein, we could hypothesize that overexpression of HSD17B4 in the oviduct of L-line rabbits could modify the estrogen concentration, changing the oviduct fluid composition and subsequently affecting the early embryonic development (Murray 1993;Killian 2004;Gad et al 2011). Similarly, changes in steroid concentration could also modify the expression of PGR, causing the desynchronization of oviductal and uterine environments and affecting the posterior development and implantation of embryos (Gad et al 2011;Waclawik 2011). ERO1L gene is involved in the "oxidation-reduction process".…”
Section: Ssh Librariesmentioning
confidence: 99%